2022
DOI: 10.3390/healthcare10101829
|View full text |Cite
|
Sign up to set email alerts
|

Eating Patterns in Children with Autism Spectrum Disorder

Abstract: The purpose of this research was to analyze the eating patterns of preschool- and school-aged children with ASD, as provided by their families, in the La Araucanía Region of Chile. It involved a cross-sectional study with 72 families with children diagnosed with ASD aged between 2 and 12 years old. Food selectivity, appetite, body mass index (BMI) and frequency of food consumption were studied. The research determined that 97.67% present food selectivity, corresponding to alterations in the frequency of consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The interaction between diet and lifestyle should be more prominently included in studies on treatment strategies for ADHD because diet and nutrition interact with other lifestyle factors, such as physical activity [41]. In addition, a survey found that 93.06%, 90.28%, 80.56%, and 62.50% of ASD children did not consume enough fruit, fish, vegetables, or water on a regular basis [42]. ADHD risk has decreased by up to 37% with a "healthy" diet high in fruits, vegetables, legumes, and fish.…”
Section: Figure 1 Nutritional Status Of the Respondents By Bmi-for-agementioning
confidence: 99%
“…The interaction between diet and lifestyle should be more prominently included in studies on treatment strategies for ADHD because diet and nutrition interact with other lifestyle factors, such as physical activity [41]. In addition, a survey found that 93.06%, 90.28%, 80.56%, and 62.50% of ASD children did not consume enough fruit, fish, vegetables, or water on a regular basis [42]. ADHD risk has decreased by up to 37% with a "healthy" diet high in fruits, vegetables, legumes, and fish.…”
Section: Figure 1 Nutritional Status Of the Respondents By Bmi-for-agementioning
confidence: 99%
“…Hasil tersebut didukung oleh penelitian Seda (2020) di mana usia yang berhubungan dengan perilaku makan secara signifikan jatuh kepada pada usia 2 -5 tahun sebesar 84,8% (P= 0,03). 14 Pada anak ASD antara usia 2 dan 5 tahun, namun penelitian ini tidak menjelaskan mengapa masalah pemberian makan anak terjadi paling banyak pada usia 4 tahun (p=0,001). Pada penelitian yang dilakukan, didapatkan sebanyak 72 (74,2%) anak berjenis kelamin laki-laki.…”
Section: Pembahasanunclassified
“…Mendive et al reported that the most significant difference between the ASD group and the TD group was the consumption of dairy products and cereals with gluten (34). Similarly, Ahumada et al observed that only 52.78% of children diagnosed with ASD meet the daily dairy recommendation, and 90.28% do not meet the fish consumption recommendation (36). For instance, Sharp et al reported that all ASD children, included in the study were at risk for inadequate intake of at least one nutrient; 78.5% were at risk for five or more nutrient inadequacies.…”
Section: Hachmeriyan Tosheva and Hadzhievamentioning
confidence: 99%